The Effect of Foreign Tourist Visits on Carbon Dioxide Emissions in the Tourism Sector in Indonesia - Hezkya Refienes Ginting (Green Publisher Indonesia, 2025)
This study analyzes the impact of international tourist visits on carbon dioxide (CO2) emissions in Indonesia's tourism sector using the Ordinary Least Square (OLS) method with time series data from 1997-2022. The results show that an increase in tourist visitation significantly contributes to CO2 emissions with a coefficient of 746.57 kilotons per person. Economic growth, number of vehicles, and fossil energy use also positively and significantly affect emissions. A 1% increase in economic growth raises emissions by 64.60 kilotons, an increase of one unit in the number of vehicles raises emissions by 9,953.66 kilotons, and fossil energy use raises emissions by 902,884.7 kilotons per kWh. In contrast, renewable energy and population size do not significantly affect CO2 emissions. Tourist transportation, particularly international flights, is a major contributor to carbon emissions. The adoption of renewable energy is still limited, making it ineffective in reducing emissions. This study highlights the importance of developing environmentally friendly tourism by strengthening the use of renewable energy and eco-friendly transportation infrastructure.